Genetic enhancement of palmitic acid accumulation in cotton seed oil through RNAi down‐regulation of ghKAS2 encoding β‐ketoacyl‐ACP synthase II (KASII). Issue 1 (7th September 2016) - Liu, Qing; Wu, Man; Zhang, Baolong; Shrestha, Pushkar; Petrie, James; Green, Allan G.; Singh, Surinder P.
Summary: Palmitic acid (C16:0) already makes up approximately 25% of the total fatty acids in the conventional cotton seed oil. However, further enhancements in palmitic acid content at the expense of the predominant unsaturated fatty acids would provide increased oxidative stability of cotton seed oil and also impart the high melting point required for making margarine, shortening and confectionary products free of trans fatty acids. Seed‐specific RNAi‐mediated down‐regulation of β‐ketoacyl‐ACP synthase II (KASII) catalysing the elongation of palmitoyl‐ACP to stearoyl‐ACP has succeeded in dramatically increasing the C16 fatty acid content of cotton seed oil to well beyond its natural limits, reaching up to 65% of total fatty acids. The elevated C16 levels were comprised of predominantly palmitic acid (C16:0, 51%) and to a lesser extent palmitoleic acid (C16:1, 11%) and hexadecadienoic acid (C16:2, 3%), and were stably inherited. Despite of the dramatic alteration of fatty acid composition and a slight yet significant reduction in oil content in these high‐palmitic (HP) lines, seed germination remained unaffected. Regiochemical analysis of triacylglycerols (TAG) showed that the increased levels of palmitic acid mainly occurred at the outer positions, while C16:1 and C16:2 were predominantly found in the sn‐2 position in both TAG and phosphatidylcholine. Crossing the HP line with previously created high‐oleic (HO) and high‐stearic (HS) genotypes demonstrated that HP and HO traits could be achieved simultaneously; however, elevation of stearic acid was hindered in the presence of high level of palmitic acid.